Modernização organizacional: liderança, competências e eficiência nas instituições públicas - Silva, Wagner Barcellos da (2024)
The modernization of public institutions and the pursuit of operational efficiency are central challenges for governments worldwide, particularly in critical sectors such as public safety and health. In the context of the increasing adoption of emerging technologies from Industry 4.0, such as Big Data, the Internet of Things (IoT), and Artificial Intelligence (AI), it becomes essential to understand how these innovations can be integrated into Competency-Based Management (GBC) practices and adaptive leadership to promote significant advancements in these sectors. In light of this scenario, this dissertation aims to analyze the impact of implementing GBC and the role of leadership in public institutions, with a focus on improving operational efficiency and professional development. To achieve the proposed objective, this research will employ a qualitative methodological approach, based on literature reviews, analyses of existing literature, and case studies. The study will consider the impact of leadership on driving GBC, the benefits of this approach for police organizations, examples of best practices, and case studies, as well as the competencies and skills of individuals involved in managing hospital supply chains and forensic police. The limitations of this study include the restricted availability of empirical data for a direct comparison between the analyzed sectors and the difficulty in generalizing results due to the contextual specificities of each institution studied. Additionally, cultural and organizational resistance to the adoption of new technologies and management methods may pose further challenges. The expected results indicate that the combination of emerging technologies with GBC practices can lead to significant improvements in operational efficiency and the professional development of public servants, creating an adaptable and innovative environment—crucial for the recognition and appreciation of forensic police professionals. This research aims to provide theoretical and practical support for public managers seeking to implement modernization and institutional development strategies